The Efficacy of Two Models of Intensive Upper Limb Training on Health-Related Quality of Life in Children with Hemiplegic Cerebral Palsy Mainstreamed in Regular Schools: A Double-Blinded, Randomized Controlled Trial. (2nd January 2023) - Bingol, Hasan; Kerem Gunel, Mintaze; Alkan, Halil
ABSTRACT: Background: Children with hemiplegic cerebral palsy (CP) are at risk of reduced upper limb function and poorer quality of life than their typically developing peers. Although upper limb impairments have potential negative impact on the health-related quality of life (HRQOL) in children with hemiplegic CP, the efficacy of upper limb rehabilitation approaches aiming to improve upper limb impairments on HRQOL has not been adequately investigated. Objective: This study compares the efficacy of two modes of activity-based upper limb rehabilitation (modified constraint-induced movement therapy [mCIMT] and bimanual training [BIM]) on HRQOL outcomes in children with hemiplegic CP mainstreamed in regular schools. Methods: Thirty children with hemiplegic CP aged between 7 and 11 years (mean age 8.53 ± 1.54 years) who had functional ability levels of I–III according to the Manual Ability Classification System (MACS), Gross Motor Classification System (GMFCS), and Communication Function Classification System (CFCS) were randomly assigned to receive mCIMT or BIM training. Result : Both mCIMT and BIM yielded statistically significant improvements in all HRQOL domains immediately after the 10-week interventions ( P < .001), which were retained at 16 weeks. Conclusion: While there were some differences in the intervention effects, both of these upper limb rehabilitation approaches based on intensive unimanual or bimanual activity may be beneficial for improving perceived life satisfaction related to physical activity, general mood, family, friends, and school among children with hemiplegic CP mainstreamed in regular schools.